Promotion of Energy use Efficiency in Lithuania - Štreimikienė, Dalia; Mikalauskienė, Asta; Širvys, Giedrius (Ekonomika, 2006)
The aim of the work was to analyse the energy efficiency measures and policies implemented in Lithuania. Energy intensity has declined 2.25 times during 1990-2004 in Lithuania, however, it is still 1.2 times higher than the EU-15 average. The increase of energy prices and implementation of EU directives targeted at energy efficiency are the main drivers of energy intensity decrease in Lithuania. The new edition of the Law on Energy adopted in 2002 regulates general activity of the energy sector, fundamentals of energy development and management and efficient usage of energy and energy resources. According to this law, promotion of energy efficiency is one of the main subjects of state regulation and policy priorities in energy. Several strategies and programmes targeted at energy efficiency increase were developed and implemented in Lithuania. The assignment from the state budget for the implementation of these programmes makes about 15 mill. Lt per year. There are several fiscals in Lithuania to promote energy efficiency in Lithuania: reduced VAT (from 18% to 9%) for insulation and modernization of buildings, feed-in prices for electricity produced from CHP. Since 1996 the Lithuanian Environmental Investment Fund provides financial support for environmentally beneficial investment projects of legal bodies duly incorporated in the Republic of Lithuania and engaged in economic activities, as well as appropriate projects of natural persons and municipalities, the implementation of which reduces the negative impact of the economic activities on the environment. The projects on energy efficiency improvement are supported by soft loans and investment subsidies. 82 mill. EUR were allocated from the EU Structural Funds (namely, the European Regional Development Fund) for the period 2004-2006 to upgrade and develop the energy transmission and distribution networks (especially District Heating networks), to increase their reliability and efficiency, to introduce renewable energy sources for electricity and heat production and to increase the efficiency of energy consumption in public buildings. The implementation of the EU ETS and Flexible Kyoto Mechanisms (Joint Implementation) in Lithuania stimulates implementation of energy efficiency measures. The white certificates system is not yet introduced in Lithuania. At present, however, the incentives provided by the Kyoto mechanisms, including the possible use in the EU ETS of credits generated through JI or CDM project activities, are not sufficient to support energy efficiency projects in Lithuania because of small-scale energy efficiency projects where the transaction costs are too high to use the JI.